Scientometrics Recent Advances - Kunosic, Suad; Zerem, Enver (IntechOpen, 2019)
In recent years, academic advancement and access to funds that stimulate scientific research have been conditioned by the scientific production of individual scientists as well as the production of scientific centers, institutes and universities. This has led to an increase in interest in the accelerated assessment and ranking of scientists and scientific institutions. Scientometry is a sub-discipline of information sciences that measures achievement in science. This book provides the reader with a detailed insight into relevant scientometric methods and criteria, their individual strengths and weaknesses in the process of ranking scientists, scientific centers and institutions, as well as their application to the process of planning scientific projects and isolated medical specialties.